2014
DOI: 10.12688/f1000research.4287.1
|View full text |Cite
|
Sign up to set email alerts
|

Histamine and acetylcholine receptor involvement in sensorimotor gating: an autoradiography study

Abstract: Sensory gating is a way by which the brain manages sensory information flow. For optimal allocation of neural resources, it is important to be able to screen out (or "gate") irrelevant sensory information when another stimulus is being processed. Sensorimotor gating more generally refers to the overall process of modulation of the motor responses to sensory stimuli. Impaired sensorimotor gating is seen in a variety of neurobehavioral disorders including schizophrenia, autism and sensory processing disorder. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 104 publications
0
1
0
Order By: Relevance
“…For example, Miller et al (McIntosh et al, 1999;Miller et al, 1999) contributed that children with SPD show increased electrodermal responses and decreased habituation while Davies and Gavin (Davies and Gavin, 2007;Brett-Green et al, 2008;Davies et al, 2009Davies et al, , 2010Gavin et al, 2011;Chang et al, 2012;Brett et al, 2016;Lagasse et al, 2019;Crasta et al) found evidence of reduced sensory gating. Utilizing rodent models to better understand the mechanisms of these electrophysiologic differences, Bauman, Levin and colleagues (Levin et al, 2005(Levin et al, , 2007Schmajuk et al, 2006Schmajuk et al, , 2009Roegge et al, 2007;Larrauri and Levin, 2012;Mahendra et al, 2012;Skefos et al, 2014;Larrauri et al, 2015;McMahon et al) determined that sensory gating deficits were related to activity of cholinergic, glutamatergic, and adrenergic receptors which suggests potential therapeutic approaches.…”
Section: Pathogenesismentioning
confidence: 99%
“…For example, Miller et al (McIntosh et al, 1999;Miller et al, 1999) contributed that children with SPD show increased electrodermal responses and decreased habituation while Davies and Gavin (Davies and Gavin, 2007;Brett-Green et al, 2008;Davies et al, 2009Davies et al, , 2010Gavin et al, 2011;Chang et al, 2012;Brett et al, 2016;Lagasse et al, 2019;Crasta et al) found evidence of reduced sensory gating. Utilizing rodent models to better understand the mechanisms of these electrophysiologic differences, Bauman, Levin and colleagues (Levin et al, 2005(Levin et al, , 2007Schmajuk et al, 2006Schmajuk et al, , 2009Roegge et al, 2007;Larrauri and Levin, 2012;Mahendra et al, 2012;Skefos et al, 2014;Larrauri et al, 2015;McMahon et al) determined that sensory gating deficits were related to activity of cholinergic, glutamatergic, and adrenergic receptors which suggests potential therapeutic approaches.…”
Section: Pathogenesismentioning
confidence: 99%